As Baianas No Carnaval Paulistano: Um Estudo Etnográfico Sobre A Ala Das Baianas Na Escola De Samba Unidos Do Peruche - Piccirillo, Nathalia Fogliati [UNIFESP] (2018)
This Essay Deals With The Construction Of The Female Bahian Figure, Which Extrapolated Its State Of Origin And Occupied A Prominent Place In The Samba Schools From Rio De Janeiro And Sao Paulo. We Have Studied The Presence Of These Women In The Development Of The Sao Paulo Carnival And, Through An Ethnographic Study With The Bahian Ward From Samba School Unidos Do Peruche, We Unveiled Its Symbolic And Historical Character, Its Identification Through Accessories, Dress Code, Body Movement, And The Notions Of Belonging And Collective Commitment.